ANALISIS ISI KARAKTERISTIK DAN SENTIMEN PEMBERITAAN ISU KENAIKAN PAJAK DI KABUPATEN PATI PADA MEDIA ONLINE KOMPAS.COM - Catur Wulan Sari Catur Wulan Sari; Yanuar Luqman (Interaksi Online, 2026)
Online news media plays a significant role in shaping public perception of government policies, including local tax policies. The Pati Regency Government under Regent Sudewo raised the Land and Building Tax Assessment Value (NJOP) by up to 250 percent, triggering widespread public resistance and drawing sustained national media attention. This situation makes the coverage patterns of Kompas.com on this issue relevant to examine systematically in order to obtain an empirical picture of how a mainstream national media outlet represents local fiscal policy to its audience. This study aims to describe the characteristics and sentiment of news coverage on the tax hike issue in Pati Regency on the online media platform Kompas.com. The study employed a descriptive quantitative content analysis method with a positivistic approach, following the principles of Klaus Krippendorff. The research object consisted of 44 Kompas.com articles containing the keywords "Pajak Pati" or "Pajak Kabupaten Pati", selected through total sampling over the period of August to December 2025. Data were collected using a structured coding sheet covering four variables: news sentiment, news intensity, issue category, and quoted sources. Intercoder reliability was tested using Holsti's formula and yielded a coefficient above 0.80 across all categories. The findings reveal that: (1) news sentiment was predominantly negative at 65.9%, followed by neutral at 29.5%, with positive sentiment at only 4.5%; (2) most articles were of high intensity at 70.5%, with zero articles classified as low intensity; (3) the dominant issue categories were politics at 34.1% and demonstrations at 31.8%, while substantive tax policy content received only 6.8%; (4) the most frequently cited sources were mass alliance groups at 25%, the Regional Parliament (DPRD) at 20.5%, and the police at 18.2%, while academics and Komnas HAM each appeared in only 4.5% of the coverage. The findings were analyzed through the framework of Attribute Agenda Setting as the primary theory, supported by Narrative Paradigm Theory and Warranting Theory. Overall, Kompas.com's coverage tended to emphasize sociopolitical conflict and drama with consistently high intensity and negative sentiment, while providing limited space for substantive policy discussion, academic perspectives, and reconciliation narratives. The author recommends that Kompas.com strengthen source diversification and balance its coverage with more substantive content, and that the Pati Regency Government improve its proactive, data-based public communication strategy.